Communicating politics : engaging the public in democratic life - McKinney, Mitchell S. (ed.) (New York, 2005)
Half of our eligible citizens fail to cast a presidential ballot and many more than half routinely ignore state and local elections. Does this phenomenon point to a crisis of democracy or does such behavior simply reflect indifference or even contentment-among the pub lic? Should we be alarmed that so many of our citizens seem disinterested and unwilling to participate in the various activities and forms of association that constitute civic life? If we are concerned by such matters, what might be done to reengage those who are seemingly disengaged? This book explores these questions and examines the well being of our civic condition at the beginning of the twenty-first century. Grounded in a communication perspective, we view the fundamen tal nature of a democracy as that of a civic dialogue an ongoing conversation between our elected leaders or political candidates and the citizens they lead or wish to lead. Accordingly, the studies presented in this vol ume examine our civic sphere and the electoral process as a communicative interaction between elected offi cials, political candidates, the media, and citizens.
Keywords: Political participation-United states